Impact of dual antiplatelet therapy duration on 1‐year clinical outcomes in diabetic patients with acute coronary syndrome undergoing percutaneous coronary intervention: Insights from the real‐world OPT‐CAD study. (23rd December 2019) - Li, Jing; Li, Yi; Qiu, Miaohan; Li, Zhiguo; Yang, Jing; Wang, Xiaozeng; Bao, Dan; Wang, Xu; Han, Yaling
Abstract: Objectives: To investigate the optimal dual antiplatelet therapy (DAPT) duration for diabetic patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). Background: Diabetic patients are at high risk for ischemic and bleeding events when treated with antithrombotic agents after an ACS episode. Methods: This post hoc study analyzed DAPT duration and clinical outcomes in diabetic patients with ACS who underwent PCI in the Optimal antiPlatelet Therapy for Chinese patients with Coronary Artery Disease (OPT‐CAD) registry. The primary outcome was patient‐oriented composite endpoints (PoCE) at 12 months; it was defined as a composite of all‐cause mortality, all myocardial infarction (MI), stroke, or any revascularization. The safety outcome was bleeding events. Results: In total, 1, 773 diabetic patients with ACS were enrolled and treated with PCI in the OPT‐CAD study. Premature DAPT discontinuation before 12 months was an independent PoCE predictor in diabetic patients (hazard ratio = 1.33, 95% confidence interval: 1.02–1.74, p = .006). It was associated with a significantly higher risk of PoCE (17.3 vs. 11.2%, p = .014) in diabetic patients with high risk factors (age ≥ 65 years or history of cardiovascular events including MI, stroke, or peripheral artery disease), but this association was not observed in those without high risk factors (10.4 vs. 9.1, p = .554). No excess bleeding risk was found in patients who received 12‐month DAPT compared with those who discontinued DAPT prematurely. Conclusions: Premature DAPT discontinuation before 12 months was associated with increased risk of clinical events in diabetic patients with ACS after PCI, particularly in those with high‐risk profiles.